2019
DOI: 10.15441/ceem.18.019
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory, cognitive, and depressive-like behaviors in adult and pediatric mice exposed to controlled cortical impact

Abstract: Objective Sequelae of behavioral impairments associated with human traumatic brain injury (TBI) include neurobehavioral problems. We compared exploratory, cognitive, and depressive-like behaviors in pediatric and adult male mice exposed to controlled cortical impact (CCI). Methods Pediatric (21 to 25 days old) and adult (8 to 12 weeks old) male C57Bl/6 mice underwent CCI at a 2-mm depth of deflection. Hematoxylin and eosin staining was performed 3 to 7 days after recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…The previous measurements in experimental TBI models mostly focused on cognitive abilities and anxiety-depression assessment. These studies indicated that cognitive deficits, anxiety-like behaviour and depression do not occur in acute and chronic periods following TBI (27,37). Our anxiety-like behaviour and depression measurements were consistent with the results of these studies.…”
supporting
confidence: 90%
“…The previous measurements in experimental TBI models mostly focused on cognitive abilities and anxiety-depression assessment. These studies indicated that cognitive deficits, anxiety-like behaviour and depression do not occur in acute and chronic periods following TBI (27,37). Our anxiety-like behaviour and depression measurements were consistent with the results of these studies.…”
supporting
confidence: 90%
“…The BMT is an efficient cognitive task test to assess spatial/non-spatial learning following CCI injury in adult mice. 31 Compared to CCI alone, additional HI aggravated spatial learning and memory. Hippocampal lesions have deleterious effects on the ability to discriminate fear-associated contexts from a neutral environment.…”
Section: Discussionmentioning
confidence: 98%
“…30 We previously reported that 2.0-mm CCI injury resulted in significant spatial learning and memory deficits when compared to sham animals. 31 Here, we employed three behavioral paradigms to assess learning and memory over 3 weeks. The BMT is an efficient cognitive task test to assess spatial/non-spatial learning following CCI injury in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…KU0063794 treatment more efficacy than rapamycin group improved latency compared with TBI group (Figure 1D,E , respectively). Additionally, as neurological deficit, increased depression and anxiety are often reported by individuals with TBI, 23 TST was performed to evaluate the neurological function. Treatment with KU0063794, more efficacy than rapamycin, leads to a significant reduction of immobility time in TBI‐injured mice (Figure 1F ), compared with TBI‐vehicle group (Figure 1F ).…”
Section: Resultsmentioning
confidence: 99%